Performance evaluation of non‐metric digital camera for photogrammetric application - Ruzgienė, Birutė (Geodesy and Cartography, 2012)
During the last year amateur low‐cost digital cameras are increasingly expected to contribute to the digital photogrammetry. An important aspect of the suitability of these cameras is determination of their geometrical instability. In order to evaluate amateur digital camera performance, small format, low resolution and low‐cost CCD camera have been investigated in two considerations: determining inner orientation parameters at different time and estimating accuracy in test field experiments. The calibration results demonstrate the poor stability of such a digital camera. As a result of the instability, amateur cameras have limited possibilities in close‐range photogrammetry. However, the investigated camera under certain limited accuracy requirements can be used for low‐accuracy photogrammetric application. First published online: 03 Aug 2012